EFEKTIFITAS PEMBELAJARAN INQUIRI BASED LEARNING PADA MATERI ASAM-BASA KELAS XI-MIA 3 SMAN 1 GUNUNGSARI DALAM MENINGKATKAN HASIL BELAJAR KIMIA TAHUN PELAJARAN 2018/2019 - SUHIRDI SUHIRDI (Universitas Mahasaraswati K. Mataram, 2021)
The research method that has been used in this research is from class action research and using the inquiry based learning as the learning style which is generally consists of two cycles. For each cycles, there are five stages that formulate the problem, stipulate the hypothesis, look for the information, draw a conclusion to thirty-one students in class XI-MIA 3 at SMAN 1 Gunungsari. The focused of this research is on subject acid base.The study uses observation, documentation and post test to collect the data. The finding shows that inquiry based learning is able to increase students learning outcomes on cycle II from cycle I. On cycle II the average post test score of the students is 75 and the percentage of learning achievents outcomes research 55% (student reached score > 70) meanwhile on cycle I, the average post test score only 73 and the percentage result is 58% (student reached > 70). The findings confirm that using inquiry based learning gives positive impact to the students at learning process